Bromine-radical-induced Csp2–H difluoroalkylation of quinoxalinones and hydrazones through visible-light-promoted Csp3–Br bond homolysis. Issue 15 (29th June 2022) - Qu, Chuan-Hua; Huang, Run; Liu, Yuan; Liu, Tong; Song, Gui-Ting
Abstract : Bromine radicals derived from photo-induced Csp 3 –Br bond homolysis can mediate H abstraction/imine radical formation from quinoxalinones and hydrazones, which in turn quench the in situ -generated difluoroalkyl radicals to furnish the products. Abstract : Disclosed herein is a photosensitizer-free strategy for the direct C–H difluoroalkylation of quinoxalinones and hydrazones with bromodifluoroacylarenes via a visible-light-promoted Csp 3 –Br bond homolytic pathway. This new reaction provides access to difluoroalkylated quinoxaline and hydrazone derivatives with excellent substrate generality under simple, mild, green, and metal-free conditions. This process exploits the fascinating photochemical activity of bromodifluoroacylarenes in the homolysis of Csp 3 –Br bonds to form difluoroalkyl radicals and bromine radical species. The generated bromine radicals can mediate H abstraction/imine radical formation directly from quinoxalinones and hydrazones, which in turn quench the in situ -generated difluoroalkyl radicals to furnish the products. It is of note is that this is the first example of the application of bromine radicals in organic transformation via Csp 3 –Br bond homolysis induced by visible light. Moreover, the minimal structural requirements for alkyl bromide-mediated photochemical Csp 3 –Br bond homolysis were investigated.